A comparative study of child begging laws in Malaysia and the United Kingdom / Deelaura Marlynatha Lawrence, Shamsiyah Azlan and Salmi Sabu - Lawrence, Deelaura Marlynatha; Azlan, Shamsiyah; Sabu, Salmi (2014)
This study explores the factors and causes of the social problem of child through the study of different laws available in Malaysia and compares it with the laws in the United Kingdom. The study's goals were firstly, to examine the adequacy and efficiency of the laws in Malaysia in order to solve the issue of child begging. The next goal is to compare the legal position between the laws in Malaysia and the United Kingdom in governing the practice of child begging and lastly to propose recommendations for the reformation of the existing laws in Malaysia in order to curb the problem. The gist of this study is the application of the scope of the laws governing the issue of child begging in Malaysia and the United Kingdom. Data were collected from multiple sources and the qualitative research method is used for this study. Data collected were from documentary evidence and also by way of guided interviews. Thus, this study presents one of the crucial advantages to stress out this issue as if the government may be alert and the society will be informed the importance of curbing this social problem nowadays. This study aims at alerting the government and the public on the importance of curbing a social problem that has become a menace to the public at large.